Gut Bacterial Composition and Functional Potential of Tibetan Pigs Under Semi-Grazing - Niu, Hui; Feng, Xi-Ze; Shi, Chun-Wei; Zhang, Di; Chen, Hong-Liang; Huang, Hai-Bin; Jiang, Yan-Long; Wang, Jian-Zhong; Cao, Xin; Wang, Nan; Zeng, Yan; Yang, Gui-Lian; et al. (Frontiers in Microbiology, 2022)
Gut bacterial community plays a key role in maintaining host health. The Tibetan pig (Sus scrofa), an ancient breed in China, has been known for its high adaptability to harsh environments and for its meat quality. To understand the underlying mechanisms facilitating to shape these unique features, in this study, 16S rRNA sequencing using pigs feces and subsequent bacterial functional prediction were performed. Also, the gut bacteria of two other breeds of pigs, Barkshire and Landrace, were examined for comparison. It was revealed that the structure of bacterial community in Tibetan pigs appeared to be more complex; the relative abundances of dominant bacterial families varied inversely with those of the other pigs, and the proportion of Firmicutes in Tibetan pigs was lower, but Bacteroides, Fibrobacterota, Lachnospiraceae, Oscillospiraceae, and Ruminococcaceae were higher. Bacterial functional prediction revealed that the dominant flora in the Tibetan pigs was more correlated with functions regulating the hosts’ immune and inflammatory responses, such as NOD-like_receptor_signaling_pathway and vitamin metabolism. In addition, in Tibetan pigs, the taxonomic relationships in the gut bacteria on day 350 were closer than those on earlier stages. Furthermore, gender played a role in the composition and function of bacterial inhabitants in the gut; for boars, they were more correlated to drug resistance and xenobiotics metabolism of the host compared to the sows. In sum, our preliminary study on the gut bacterial composition of the Tibetan pigs provided an insight into the underlying host–microorganism interactions, emphasizing the role of intestinal bacteria in the context of modulating the host’s immune system and host development.